Jugoslovanske vizije tržaških Slovencev v obdobju 1912-1913 - Ivašković, Igor (Studia Historica Slovenica, 2017)
The author describes factors of the Yugoslav idea among Slovenians Trieste in the period of before and during Balkan wars in 1912-1913. At first, Slovenians were in favour of a South Slav unit within the Habsburg Monarchy. This political platform included the alliance with a part of Croatian politicians. However, the Balkan wars encouraged Slovenians to develop a broader South Slav political framework, which included integration of Habsburg South Slavs with other Balkan Slavs. The developments on the battle field during 1913, however, forced Slovenians from Trieste to reduce their political framework and exclude Bulgarians from envisaged South Slav state.
Keywords: Avstro-Ogrska; balkanske vojne 1912-1913; narodne manjšine; Slovenci; Trst